Expansion Points Intervention in Young Children with Speech Sound Disorders: A Multiple Baseline Design - Brumbaugh, Klaire M.; Gibson, Ashley (Seminars in Speech and Language, 2021)
The purpose of this investigation was to evaluate the efficacy of expansion points (EXP) intervention with a modified criterion for preschool children with speech sound disorders (SSD). Three preschool-aged children were enrolled in a single-subject multiple baseline intervention study. Intervention took place over 16 sessions. Pre- and post-intervention data are provided. Three outcome measures (generalization to probe words and gains in percent consonants correct, PCC, in words and in conversation) were evaluated to measure the effectiveness of the EXP intervention. All three of the participants demonstrated gains by the end of the intervention phase when measuring PCC in single words. Two of the three participants demonstrated gains in PCC in conversational speech. Progress on individual phonemes was variable across participants. Utilizing the EXP approach, two of the three children showed gains in all three outcome measures. One child showed variable performance in one outcome measure, improvement in one, and a decrease in one. Findings suggest that EXP should be further explored to evaluate intervention efficacy.
Keywords: speech sound disorders; preschool; expansion points intervention; single subject research design